(untitled) (Studies in Comparative Education, 2024)
This study aims to examine the role of career well-being in the context of career guidance and education in Finnish secondary schools. It was found that the Finnish approach takes into account not only education but also the development of students’ career prospects, and this plays a key role in their overall well-being. The article aims to identify the importance of career well-being as a key aspect of career guidance and education in Finnish general education institutions. Various general scientific and pedagogical methods were used in the course of the scientific research. The theoretical methods included analysis, systematic, analytical-synthetic, which were used to substantiate the content of career well-being as a key aspect of career guidance and education in Finnish secondary schools. Among other theoretical methods, synthesis, including general scientific, was used. These methods were also used to formulate conclusions and develop principles, aspects, systematization and generalization in order to create content generalizations of theoretical material and determine conceptual provisions. The main findings of the article indicate that the system of career guidance and education in Finnish secondary schools requires attention to the individual needs of students. It was found that a lack of provision in this area can lead to inconsistencies between the educational process and real expectations in the labor market. In particular, it was determined that there is insufficient support for students in the development of personal and professional competencies, which can complicate their definition of career goals and successful entry into the world of work. Additionally, the results indicate limited interaction between educational institutions and employers in the process of preparing students for career development. This creates gaps in the acquisition of practical skills and internship opportunities, which affects the readiness of graduates to effectively enter the professional sphere. The conclusion of the article is that the development of the system of career guidance and education in Finnish secondary schools is critically important for the effective preparation of students to choose their career path. It is necessary to emphasize the individual needs of students, providing them with comprehensive support and development of not only technical but also social skills for maximum entry into the labor market.